Experimental corrections in neutron scattering experiments: A modern theoretical and computational approach - Dawidowski, Javier (2014)
Experimental corrections in neutron scattering are a longstanding issue tha t has been addressed in different ways acc ording to the resources available in each age. Sin ce computational resources are not a constraint at present, the early approaches based on theoretical approximations have led to today’s computational methods based on numerical simulations. At the base of all the corrections, we must fi nd a numerical method and a suitable model of the neutron interaction with the system. Wit h regard to simulations, the demands posed by different experimental techniques, should lead to the design of specifi c solutions for each particular case, while models describing the interaction should include a wide variety of systems. In the Neutron Physics Department at Bariloche Atomic Center (Argentina), both issues were addressed for more than two decades. On the one hand, the development of models describing the interaction of neutrons with molecular and solid systems, has helped to strengthen the methods of analysis of various neutron techniques, and has fed nuclear data libraries of extensive employment in the area of Nuclear Engineering. On the other hand, the numerical simulation methods developed were applied in the analysis of very diverse experiments such as diffraction, inelastic neutron scattering, spectroscopy and electron-volt spectroscopy, and were successfully applied in experiments performed at Bariloche, as well as at ILL and ISIS. Moreover, we have validated the role of the technique of neutron transmission (to obtain the total cross section), as a reference tool in the process of absolute normalization of the experimental data, a rarely stated goal in the context of modern neutron scattering techniques.